Institutional Collaboration as Essential Ingredient for Good Governance, Efficient and Effective Service Delivery in a Democracy: A Critical Discourse (Global Journal of Human-Social Science, 2012)
Democracy governance process and the accompanying politics in real sense largely consist of the examination and maintenance of the ways in which constitutional political and administrative institutions social forces and movementss in a particular society interact with each other of limits upon the extent to which stable constitutional modes of behavior can be developed and of the effects they can have on molding behavior for a productive and mutually beneficial holistic existence of the state This has been largely so and still expected of the state This has been Largely so and still expected to be so in that under the federal governmental system each citizen is represented by at least three federal state and local governments as well as a myriad of other interests
Keywords: Democracy; administrative; beneficial; interests